PENGABDIAN MASYARAKAT KEPADA PELAKU UNIT BISNIS BUMDESA BAHAGIA MELALUI PELATIHAN SMART QASIR APPLICATION GUNA MENINGKATKAN LAYANAN KEUANGAN CAFé SAELO SIDOMULYO - Mulyono, Resha Dwi Ayu Pangesti; Afandi, M. Farid; Prasetyo, Herry; Rosa, Dien Vidia; Aprillianto, Bayu (Abdi Panca Marga, 2023)
Cafe Saelo is part of the BUMDESA Bahagia business unit located in Sidomulyo Village, Silo District In transaction service activities at Café Saelo which is part of the business unit of BUMDESA Bahagia still uses manual recording where sometimes there are still errors by the financial department. The problem that arises is often also that Café Saelo does not calculate how much sales results in real time and café needs that match consumer demand well. So in this case the service team has the initiation to use the Smart Qasir application by mapping menus and recording financial transactions. This program aims to introduce and train Café employees with the Smart Qasir application in recording sales, mapping technology-based café set menus so as to get real time information every time there is a sale. The method carried out is mapping the set menu sold at the café, financial transactions, especially making sales reports by discussing with the cashier and treasurer of the café. The result is to create technology-based sales reports with the Smart Qasir application for Cafe Saelo employees. This output is also expected to be part of the needs of partners to be able to make café financial statements that are integrated with BUMDESa Bahagia Sidmulyo so that reports are transparent. KeywordS: Financial Transactions, Qasir Smart App, Transparency